SPWM Inverter with Closed Loop Control System to Maintain Constant Load Voltage at Variable Load Condition - Prasanna Sapkota; Sachin Yadav; Sabin Pudasaini; Indraman Tamrakar (KEC Journal of Science and Engineering, 2025)
AC is the predominant form of electrical power consumption, inverters have been widely used for residential, commercial and industrial applications such as uninterruptible power supply (UPS) and AC motor drives etc. Reliable conversion of electric power is very important in these various applications. This project, “Design and Fabrication of SPWM Inverter with Closed Loop Control System to Maintain Constant Load Voltage at Variable Load Condition” aims to build a closed loop SPWM inverter to provide a reliable conversion of electric power by providing constant load voltage at variable loading conditions. This is done by constantly monitoring the output voltage of the inverter. The change in load either increases or decreases the voltage at the output side of the inverter. This change in output voltage is monitored through a feedback mechanism. The inversion of electric power is controlled through the SPWM mechanism so that the monitored effect in the output voltage is considered and essential actions are taken to keep the output voltage of the inverter constant. The design and tuning of the system are done through simulation software MATLAB Simulink and Proteus 8 professional.